MAINTAINING DISCIPLINE AMONG MILITARY AND CIVILIAN POLICE OFFICERS IN INTERNATIONAL PEACEKEEPING MISSIONS AND THE ACTIVITIES OF THE UNITED NATIONS MILITARY POLICE - Zarosylo, Volodymyr; Kryutchenko, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the scientific research is to analyze the experience of military police units in international peacekeeping missions and formulate proposals for reforming the military law enforcement service in Ukraine. The scientific article examines the issues of creating and organizing the activities of military police in international peacekeeping missions in the territory of the former Yugoslavia. Discussion: the analysis shows that international peacekeeping missions in the territory of the former Yugoslavia became the largest in the history of the United Nations in terms of deployment. More than 200 thousand military and civilian police officers participated in the missions. At the beginning of the deployment of international peacekeeping missions in the territory of the former Yugoslavia, an attempt was made to create military police on the model of such formations in most countries of the world. However, experience has shown that military police in international peacekeeping missions in the territory of the former Yugoslavia were unable to work due to various circumstances, including the following: lack of decisions by the United Nations on the creation of the aforementioned units in international peacekeeping missions; lack of a common vision of the activities of the military police among the commanders of military contingents and civilian police commissioners; lack of a unified approach to the powers of the military police on the part of the countries participating in international peacekeeping missions; different levels of training of military personnel and civilian police officers who were sent from different countries to participate in international peacekeeping missions. To date, the issue of the activities of military police units in the territory of international peacekeeping missions that are operating has not been resolved. The issue of bringing military personnel and civilian police officers who commit administrative and criminal offenses on the territory of international peacekeeping missions is resolved directly by the command of national contingents, however, in the vast majority of cases of such offenses, the greatest punishment for their commission is the deportation of the perpetrators to the territory of the countries that sent them to the missions. Results: it is substantiated that the creation of relevant military police units on the territory of international peacekeeping missions is a rather complex issue and requires detailed consideration and agreement with all participants in international peacekeeping missions and the leadership of the United Nations.